2019
DOI: 10.1002/ange.201911686
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Dearomatization of Indoles by an Azoalkene‐Enabled (3+2) Reaction: Access to Pyrroloindolines

Abstract: The enantioselective dearomatization of indoles by an organocatalytic (3+2) reaction has been established. The reaction makes use of simple indole derivatives as substrates, and employs azoalkenes reaction partners. A wide range of pyrroloindolines containing an all‐carbon quaternary stereogenic center were readily prepared in high yields and with excellent enantioselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 115 publications
0
3
0
Order By: Relevance
“…Therefore, given the results with the use of both 2,3- and 3-unsubstituted indoles (associated with the [4 + 2] pyridazine-ring-opening reaction) and to further showcase the flexibility of this catalytic annulation strategy, we next moved our attention to exploring the reactivity of C3-blocked indoles ( e.g ., 3-substituted and 2,3-disubstituted indoles) with DDs. To our surprise, the reaction of 3-methyl indole ( 1p ) with linear DD 2n led to a mixture of two cycloadducts, the expected tetrahydro-1 H -pyridazino[3,4- b ]indole compound 3ab and the tetrahydropyrrolo[2,3- b ]indole compound 5a ( 14 ) in a ratio of approximately 1:1, which could possibly be the result of the above-mentioned two competitive reaction pathways 15 ( Scheme 2 ). Interestingly, when 1,3-dimethyl indole ( 1q ) was used in combination with DD 2j , the exclusive formation of product 5b (46% yield) was detected.…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, given the results with the use of both 2,3- and 3-unsubstituted indoles (associated with the [4 + 2] pyridazine-ring-opening reaction) and to further showcase the flexibility of this catalytic annulation strategy, we next moved our attention to exploring the reactivity of C3-blocked indoles ( e.g ., 3-substituted and 2,3-disubstituted indoles) with DDs. To our surprise, the reaction of 3-methyl indole ( 1p ) with linear DD 2n led to a mixture of two cycloadducts, the expected tetrahydro-1 H -pyridazino[3,4- b ]indole compound 3ab and the tetrahydropyrrolo[2,3- b ]indole compound 5a ( 14 ) in a ratio of approximately 1:1, which could possibly be the result of the above-mentioned two competitive reaction pathways 15 ( Scheme 2 ). Interestingly, when 1,3-dimethyl indole ( 1q ) was used in combination with DD 2j , the exclusive formation of product 5b (46% yield) was detected.…”
Section: Resultsmentioning
confidence: 96%
“…A large number of new reviews [ 26 , 27 , 56 , 57 ] and original publications [ 31 , 58 , 59 , 60 , 61 , 62 ], which appeared in the last four years, demonstrates the growing interest in the chemistry of azoalkenes and their applications in hetero -Diels-Alder reactions. The presented study showed important mechanistic aspects and demonstrated that scarcely known 3,6-dihydro-2 H -1,3,4-thiadiazines can efficiently be prepared by regioselective hetero -Diels-Alder reactions of thioketones with in situ-generated azoalkenes, bearing an electron-withdrawing substituent at the terminal N-atom.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, Lu et al established the first metal-free enantioselective dearomatization addition of indoles 210 to access chiral pyrroloindoline cores 220 (Scheme 61). [70] Such a convergent approach takes utmost care to highly reactive conjugated azoalkenes 219 as an exceptional reaction partner. The reaction was performed under mild reaction conditions, and over a wide range of pyrroloindolines 220 were obtained in good to excellent yields and with excellent.…”
Section: Through Chiral Phosphine-/phosphoric Acid-catalysismentioning
confidence: 99%